Parc National Du Banco, Un Patrimoine Entre Destruction Et Conservation : Realite Et Enjeux D’une Gestion Durable - Claude, Akoue Yao; Sinan, Adaman; Alphonse, Zon Dehenouin (European Scientific Journal, ESJ, 2017)
Forest protection and conservation in Ivory Coast and its ressources were always been in political concern. That is why since its independance, Ivory Coast created an important network of protected areas in order to preserve its forest cover and its biodiversity. In spite of these efforts of forest conceptualization, the situation remains in crisis. Indeed the share of the National parks and Reserves undergo deep changes related to the anthropic pressures. Created in 1953 and located in the heart of the economic capital of the Ivory Coast, the National Park value does not escape such a situation. Indeed, the activities undertaken by populations living around this park and the fast urbanisation of the town of Abidjan represent an obstacle to the survival of the park. To suppress this situation, political measurements are installed for better managment of this park. This study aims to analyze the threats related to urban pressure on this park.